PUPPET FOR TEACHING SPEAKING NARRATIVE TEXT TO THE EIGHTH GRADERS (RETAIN, 2013)
Speaking English is not easy for the most students in our nation. There are many reasons which make our students get the difficulties when they have to speak in English. For that reason, the English teachers have to find the ways to teach this skill easily. Using puppet is the one way to teach speaking English. Puppet means the media which is made to show the character. In this matter, the use of puppet will make the students show the character through speaking in narrative text. This study attempts to answer two research questions dealing with the implementation of puppetry in teaching speaking. The questions are; first, How puppet is implemented in the teaching of speaking narrative text, second, How are the students’ responses after the implementation of puppetry in teaching speaking narrative text. Since this study was descriptive qualitative, the writer would describe and analyze the existing phenomena during the study. In this case, the study was done in three meetings which took the eighth graders of junior high school as the subject of the study. The place of the study was at SMPN 31 Surabaya. Furthermore, there were three kinds of instruments used in this study; they were observation checklist, interview, and questionnaire. Based on the findings, the writer noticed that the activities during the implementation of puppet greatly varied. At the first meeting, the class was held in the classroom. The teacher explained about narrative text. While at the second meeting, the class was held in the library. The teacher explained about puppet and demonstration it. The last meeting was held in the class and the students had to perform puppet show and the teacher acted as the supervision and also gave the evaluation. The notes were about the analysis of teaching learning activities, and the media used. In addition, the implementation of puppet helped the students in teaching learning process, especially in speaking narrative class. The evidence could be shown in the students’ responses. The result of questionnaire showed that the students mostly interested in puppet, agreed that it was helpful in making the students speak in English. Key words: speaking, puppet, narrative text, speaking narrative text